Penerapan Media Pembelajaran Mentimeter untuk Meningkatkan Minat Belajar Siswa pada Mata Pelajaran Pendidikan Pancasila di SMAN 1 Kadugede - Nurhayati, Ita; Ahmad Fajri Lutfi (Indo-MathEdu Intellectuals Journal, 2025)
This study is based on the importance of using technology in learning and the need to increase students' interest in Pancasila Education material. The purpose of this study is to determine how the use of Mentimeter learning media affects the increase in students' interest in Pancasila Education subjects at SMAN 1 Kadugede. This study was conducted through a quantitative experiment. The study involved 394 students in grade X at SMAN 1 Kadugede, with 72 students from class XD (control) and XJ (experimental) used as the sample. Data collection techniques included observation, interviews, documentation, and questionnaires. Data analysis techniques included validity, reliability, normality, homogeneity, paired sample t-test, and independent sample t-test using SPSS. The results of the study indicate that the use of Mentimeter influences students' desire to learn about Pancasila Education. The pretest questionnaire results increased from 46.72 to 52.61 on the posttest questionnaire, showing a difference in the average score between the pretest and posttest questionnaires of 5.89. The data collected shows that students' responses to the results of using the Mentimeter learning tool are positive.